Hemorrhagic stroke in Saudi adult male population and the ABO blood group distribution: a comparative analysis - Farshori, Mohammad P.; Alrashdan, Yasir G.; Alshammari, Mohammed S. (International Journal Of Community Medicine And Public Health, 2020)
Background: Globally stroke is leading cause of death and disability. According to WHO every year 15 million people get stroke and one third of these subjects die and about 5 million become permanently disabled. In SA smoking, diabetes, and hypertension are highly prevalent and since these factors are among ten major risk factors for stroke it puts Saudi population at higher risk of stroke. In current study we studied prevalence of hemorrhagic (HS) stroke and analyzed if there is any correlation between incidences of HS and ABO blood groups in Saudi population. Methods: Blood groups and other relevant data were collected for 2304 stroke patients registered at King Khaled hospital between 1/1/2008 to 1/6/2018. Statistical analysis was performed using Z calculator. Results: We saw 5.4-fold increase in prevalence of diabetes type 2 and 8.7 fold increase in prevalence of hypertension among HS patients as compared to control subjects. Prevalence of smoking was higher in both control and HS patients. 21.7% of stroke patients were HS patients. Distribution of A blood group was significantly higher in male HS patients. AB blood group showed statistically significant reduction in HS patients as compared to control group. Results were statistically significant at (p˂0.01). However, blood group B and O showed no significant differences between two groups. Conclusions: Results of our studies show a correlation between ABO and the incidences of hemorrhagic stroke in Saudi adult male population. Larger studies are needed to confirm these results.